Physical abilities of students with different years of volleyball training - Skorosov K.K. ,; Medvedev I.N. ,; Ermolina N.V. ,; Zubko E.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to trace the changes in the physical fitness of university students during their lessons in the volleyball section. Methods and structure of the study. Thirty-two clinically healthy male university students were examined. Standard tests were used with calculation of Student's criterion on their results. Results and conclusions. Students who started volleyball training initially had low physical abilities. As the length of volleyball training increased, the students improved the results of all applied tests. After 9 months of training, volleyball players had the highest results in all physical ability tests. Regular long-term training in the volleyball section provides an opportunity to obtain significant progress in the level of physical abilities of students, stimulating the reserves of their internal organs, which contributes to the growth of their intellectual potential. The achieved effects contribute to increasing the efficiency of their learning process at the university and thus improve the quality of training of future professionals of their work, capable of long-term fruitful labor.